Zoom Fatigue Among Undergraduate Nursing Students: A Descriptive Study - Kurniawan, Moh Bagus; Sutono, Sutono; Harjanto, Totok (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: The COVID-19 pandemic has disrupted the global education system. The School of Nursing at UGM enforced a transition from face-to-face to blended learning. Delivery of synchronous online learning by utilizing video conferencing applications can trigger fatigue, hereafter referred to as Zoom fatigue. Fatigue may pose a physical and mental risk to students' social functioning and perceived safety; it may also decrease their ability to deal with problems and limit opportunities for fulfilling social needs. Therefore, evaluating Zoom fatigue among nursing students at the Faculty of Medicine, Public Health, and Nursing UGM is necessary. This study aims to describe Zoom fatigue among undergraduate students at the School of Nursing at UGM during the COVID-19 pandemic based on Zoom fatigue dimensions.Methods: This research is a quantitative descriptive study with a cross-sectional design. A total of 188 students from the second, third and fourth years were recruited with stratified random sampling. The Zoom Exhaustion and Fatigue Scale (ZEF) questionnaires tested for content validity and reliability with Cronbach alpha=0.909 were distributed to the students through Google Forms. Retrieved data in this study was explored using computer-based data analysis.Results: A total of 98 students (52.1%) were reported to have severe Zoom fatigue. Based on the five dimensions of fatigue, most participants (72.9%) suffered from general fatigue. Emotional fatigue was indicated in 122 students (64.9%), followed by social fatigue with 115 students (61.2%), motivational fatigue with 102 students (54.3%), and eyestrain with 99 students (52.7%).Conclusion: Undergraduate students at the School of Nursing at UGM suffered from severe Zoom fatigue, especially in the general fatigue dimension.